2023
DOI: 10.1007/s11154-023-09839-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between thyroid and human-associated microbiota: A systematic review of reviews

Camilla Virili,
Ilaria Stramazzo,
Maria Flavia Bagaglini
et al.

Abstract: In recent years, a growing number of studies have examined the relationship between thyroid pathophysiology and intestinal microbiota composition. The reciprocal influence between these two entities has been proven so extensive that some authors coined the term "gut-thyroid axis". However, since some papers reported conflicting results, several aspects of this correlation need to be clarified. This systematic review was conceived to achieve more robust information about: 1)the characteristics of gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 131 publications
0
1
0
Order By: Relevance
“…Numerous studies have been performed to explore the relationship between intestinal microbiota and diseases, such as gastrointestinal diseases, psychiatric diseases, metabolic diseases, and autoimmune diseases (Tlaskalová-Hogenová et al, 2011 ; Chen et al, 2016 ; Vitale et al, 2021 ). Some studies have indicated the association between gut microbiota and thyroid diseases, along with the concept of “thyroid–gut–axis” (Lerner et al, 2017 ; Fröhlich and Wahl, 2019 ; Jiang et al, 2022 ; Virili et al, 2023 ). However, whether the alteration of microbiota is the cause of thyroid diseases cannot be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed to explore the relationship between intestinal microbiota and diseases, such as gastrointestinal diseases, psychiatric diseases, metabolic diseases, and autoimmune diseases (Tlaskalová-Hogenová et al, 2011 ; Chen et al, 2016 ; Vitale et al, 2021 ). Some studies have indicated the association between gut microbiota and thyroid diseases, along with the concept of “thyroid–gut–axis” (Lerner et al, 2017 ; Fröhlich and Wahl, 2019 ; Jiang et al, 2022 ; Virili et al, 2023 ). However, whether the alteration of microbiota is the cause of thyroid diseases cannot be determined.…”
Section: Introductionmentioning
confidence: 99%